VLOGGER-BOYS AND VLOGGER-GIRLS! LINGUISTIC AND STYLISTIC CHARACTERISTICS OF GENDER AS A SOCIAL FACTOR IN THE SPEECH OF BULGARIAN SOCIAL MEDIA - Asya CHAMOVSKA; Sofia MITSOVA (Езиков свят, 2025)
This paper presents a study carried out through a combination of correlative and behavioral approaches of the characteristics of male and female speech styles. The research is based on social media monitoring. At the end of the 1990s, the American sociolinguist Deborah Tannen summarized after many years of included observations in a natural environment that women and men, as representatives of social groups determined by sex, demonstrate differences in their speech and behavioral styles. The main goal of this study is to proceed to what extent Tannen's conclusions apply to the Bulgarian speech and social reality some thirty years later and in a new communicative environment - the online communicative environment of social media. According to a methodology developed by the authors of the paper, sociolinguistic monitoring of publicly available vlogs on the YouTube internet platform was carried out. According to predetermined sociolinguistic factors such as gender and age, vlogs of 9 young women and 9 young men were selected, and a classification of common linguistic and stylistic features in the speech appearances of the vlogger informants was made. The conclusions of the conducted research after analysis of the language material and performed classification are that the speech, stylistic and behavioral features described by Tannen in the linguistic manifestations of men and women, both in the 1990s, and today - in the communication conditions of the 2020s, have not undergone any particular changes.